2001
DOI: 10.1046/j.1460-9592.2001.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of 50%/50% Versus 65%/65% Tilt Biphasic Waveform on Defibrillation in Humans

Abstract: It is unknown if there is a single optimal biphasic waveform for defibrillation. Biphasic waveform tilt may be an important determinant of defibrillation efficacy. The purpose of this study was to compare acute defibrillation success with a three-electrode configuration in humans using 50%/50% versus 65%/65% tilt truncated exponential, biphasic waveforms delivered through a 110-microF capacitor. Acute DFTs for biphasic waveforms with 50%/50% versus 65%/65% tilt were measured in random order in 60 patients usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…For fixed‐tilt waveforms, duration depends on the waveform time constant. The performance of some fixed‐tilt waveforms can be improved either by different waveform truncation based either on tilt 129 or duration 130–132 . For commercial ICDs with fixed duration waveforms, initial recommended programming is based on an estimated cardiac membrane time constant of 3.5 ms 130–132 .…”
Section: Factors That Influence Required Defibrillation Shock Strengtmentioning
confidence: 99%
“…For fixed‐tilt waveforms, duration depends on the waveform time constant. The performance of some fixed‐tilt waveforms can be improved either by different waveform truncation based either on tilt 129 or duration 130–132 . For commercial ICDs with fixed duration waveforms, initial recommended programming is based on an estimated cardiac membrane time constant of 3.5 ms 130–132 .…”
Section: Factors That Influence Required Defibrillation Shock Strengtmentioning
confidence: 99%
“…Those studies found that lower DFTs at lower tilts have smaller system time constants, and those not demonstrating an effect have had relatively higher time constant. Natale et al and Sweeney et al both reported lower DFTs when tilt was lowered to 50% from 65% utilizing a biphasic waveform with three‐electrode systems (110‐μF capacitor) 3,4 . These studies had system time constants less than 5 ms (4.8 and 4.1, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have examined options for alterations of biphasic waveforms for currently available cardioverter defibrillators 1–6 . Conventional implantable cardioverter defibrillators (ICDs) deliver a biphasic waveform which is truncated after the voltage has declined exponentially by 50–65% of the initial value 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient received propofol for anesthesia and a minimum interval of 5–6 minutes was used between each test. For the first attempt, the tilt of the defibrillating waveform was reprogrammed from 65% to 50%, 6 the shock failed, and the patient was externally defibrillated. Other attempts were made with and without the superior vena cava (SVC) coil, but a consistent DFT between 25 and 27 J (740 V) could not be obtained in order to achieve adequate safety margins (Table I).…”
Section: Case Reportmentioning
confidence: 99%